Association of Antidepressant Medication Type With the Incidence of Cardiovascular Disease in the ARIC Study. Issue 11 (4th June 2019) - Almuwaqqat, Zakaria; Jokhadar, Maan; Norby, Faye L.; Lutsey, Pamela L.; O'Neal, Wesley T.; Seyerle, Amanda; Soliman, Elsayed Z.; Chen, Lin Y.; Bremner, J. Douglas; Vaccarino, Viola; Shah, Amit J.; Alonso, Alvaro
Abstract : Background: The association of antidepressant medication type with the risk of cardiovascular disease (CVD) is unclear. We hypothesized that selective serotonin reuptake inhibitors (SSRIs) are associated with lower risks of CVD events relative to tricyclics and other non‐SSRI antidepressants. Methods and Results: We studied 2027 participants from the ARIC (Atherosclerosis Risk in Communities) study (mean age 63±10 years; 29% men; 78% white) treated with antidepressants at some time between 1987 and 2013. Antidepressant usage was confirmed by participants bringing pill bottles to study visits. CVD events in the study sample were identified, including atrial fibrillation, heart failure, myocardial infarction, and ischemic stroke. Hazard ratios were used to compare CVD events adjusted for sociodemographic and clinical risk factors in SSRIs users (47%) versus non‐SSRI users. Participants were followed from antidepressant initiation up to 2016 for a median of 13.5 years. We identified 332 atrial fibrillation, 365 heart failure, 174 myocardial infarction and 119 ischemic stroke events. CVD risk was similar for SSRIs and non‐SSRI antidepressant users (hazard ratio, 1.10; 95% CI, 0.86–1.41 for atrial fibrillation; hazard ratio, 0.98; 95% CI, 0.77–1.25 for heart failure; hazard ratio, 0.91; 95% CI, 0.64–1.29 for myocardial infarction; and hazard ratio, 1.07; 95% CI, 0.70–1.63 for ischemic stroke). Conclusions: SSRI use was not associated with reduced risk of incident CVD compared with non‐SSRI antidepressant use. These results do not provide evidence supporting the use of SSRIs compared with tricyclics and other non‐SSRI antidepressants in relation to CVD risk.